Family Support and Diabetic Distress in Diabetes Mellitus Type-2 Patients - Anita, Diyah Candra; Ilyas, Aura Risky Putri; Wantonoro, Wantonoro (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2025)
Diabetes distress can significantly impact a person's mental health and motivation to manage the disease. Family support can reduce diabetes distress by providing comfort and understanding. This study aims to determine the relationship between family support and diabetes distress in type-2 diabetes mellitus patients at PKU Muhammadiyah Gamping Hospital, Indonesia.This study adopted a descriptive correlational design with a cross-sectional design. Samples were taken by accidental sampling technique from the population of outpatients at the PKU Muhammadiyah Gamping Hospital Polyclinic, with 107 respondents. The research instrument used was a family support questionnaire and the Diabetes Distress Scale-17. Data analysis was performed using Kendall's Tau correlation test. The results showed that most respondents had good family support (88.8%) and no distress (58.9%). Kendall's Tau correlation test showed a significant relationship between family support and diabetes distress with a P value = 0.014 and a correlation coefficient = 0.229. There is a significant correlation between family support and diabetes distress in patients with type-2 diabetes mellitus at PKU Muhammadiyah Gamping Hospital. Good family support can reduce diabetes distress in patients.